Peningkatan Keputusan Investasi Saham Melalui Pendapatan Dan Literasi Keuangan - Ni Putu Yuliana Ria Sawitri; Ni Nyoman Sudiyani; I Gusti Agung Prabandari Tri Putri (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2023)
The purpose of this research is to find out whether financial literacy is able to mediate the effect of income on investment decisions. The object of this research is investors who open accounts through the Ngurah Rai University Investment Gallery. The population in this study are all investors in the Ngurah Rai university investment gallery from 2019 to 2022, a total of 616 investors. The number of samples is 86 people. The data in this study were analyzed using the SEM-PLS technique. The results of the research conducted show that: a) Income has a positive and significant effect on the investment decisions of Ngurah Rai University students. b) Financial literacy has a significant positive effect on the investment decisions of Ngurah Rai University students. c) Financial literacy is not able to moderate the effect of income on the investment decisions of Ngurah Rai University students.